The Impact of Electronic Payment Methods on the Financial Performance of the Economic Institution (Journal of Economic Additions, 2025)
This study examines the impact of electronic payment methods on the financial performance of Ooredoo, a Qatari economic institution, during 2017–2024. Customer value was used as an indicator of electronic payments, while revenues measured financial performance. Statistical significance tests confirmed a meaningful correlation, and regression analysis clarified the relationship. The Granger causality test further explained the direction of influence. Results show a statistically significant link, indicating that electronic payment methods enhance Ooredoo’s financial performance, particularly in the long term.Jel Classification Codes: G21, E42, L81.
Keywords: Electronic payment methods; financial performance; statistical significance.